2002
DOI: 10.1097/00019501-200206000-00006
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo biocompatibility evaluation of stents coated with a new biodegradable elastomeric and functional polymer

Abstract: This study suggests that the newly developed copoly(ester-amide) elastomers may be suitable for stent-based local drug delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 20 publications
5
55
1
Order By: Relevance
“…In particular, copoly(ester amide)s based on -amino acids (e.g., L-leucine and L-lysine), diols and dicarboxylic acids were demonstrated to be biocompatible with the arterial walls [90,91]. Furthermore, PEAs coatings loaded with a 50% of tempamine had a tendency to decrease arterial injury as demonstrated by in vivo studies, in contrast with the severe inflammation observed when stents were directly loaded with the drug (i.e., without using the polymer coating) [92].…”
Section: Drug Delivery Systemsmentioning
confidence: 99%
“…In particular, copoly(ester amide)s based on -amino acids (e.g., L-leucine and L-lysine), diols and dicarboxylic acids were demonstrated to be biocompatible with the arterial walls [90,91]. Furthermore, PEAs coatings loaded with a 50% of tempamine had a tendency to decrease arterial injury as demonstrated by in vivo studies, in contrast with the severe inflammation observed when stents were directly loaded with the drug (i.e., without using the polymer coating) [92].…”
Section: Drug Delivery Systemsmentioning
confidence: 99%
“…To allow a controlled drug release, a variety of biomaterials/polymers such as copoly(ester-amide)elastomers [77] and phosphorylcholine have been tested especially with view to drug release fromulas, a reduction in platelet and protein adhesion, and the capability of an endothelialization of the stent [78 -81]. Progress with such polymers has founded the era of drug-coated stents.…”
Section: Drug-dose Response and Latencies In Vivomentioning
confidence: 99%
“…For example, biodegradable elastomeric scaffolds enable the construction or modelling of several soft tissues that include blood vessels, cartilage, smooth muscle cells and cardiovascular tissue [13,14]. Besides that, different implantable devices such as stents, sutures and biosensors can contain biodegradable elastomer parts integrated within their design [15][16][17]. Actifit™ is a segmented aliphatic PU based on poly(ε-caprolactone) (PCL), and 1,4-butane diisocyanate (BDI), which has recently arrived on the market.…”
Section: Introductionmentioning
confidence: 99%